Reconocimiento de Facial basado en FPGA - Molina y Cols., Julio C (2019)
The image analysis is a subject on which much emphasis is being given with purpose of identifying parameters, data, visual features in the image that provide us information about environment, it is represented in the image, but without the intervention of a person. Many methods have been developed with passing of the years, each seeking to minimize the error. The vast majority of implementations of these Facial Recognition Systems have been in a computer and a few have been implemented on hardware. This paper presents a Face Recognition System based on FPGA, The FPGA is configured with the language VHDL, this system is independent of a computer, this will give the system based on FPGA three main advantages, which include fast processing thanks to the ability of the FPGA that can perform parallel processes, and the other two advantages are the size and weight that are important to have more limited applications in weight and size.